Dicrostonyx nelsoni Merriam 1900 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Dicrostonyx nelsoni Merriam, 1900. Proc. Wash. Acad. Sci., 2:25. TYPE LOCALITY: U.S.A., Alaska, Norton Sound, St. Michael. DISTRIBUTION: W. coastal Alaska and Alaska Peninsula. COMMENT: Tentatively includes peninsulae; see Youngman, 1975, Mammals of the Yukon Terr., Nat. Mus. Can. Publ. Zool., 10: 115 (has not been karyotyped (RSH)). Range poorly known; diploid number is 30 for males and females and the fundamental number is 54; formerly included in torquatus; see Rausch, 1977, in Sokolov, ed., [Adv. Mod. Theriol.], Acad. Sci. U.S. S.R., Nauka, Moscow, pp. 162- 177; or groenlandicus; see Hall, 1981:836. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 483, DOI: 10.5281/zenodo.7353034